Internationalization of a regional university - Inna V. Ryzhkova; Aleksandra V. Burtseva (Высшее образование в России)
The article covers peculiarities of internationalization proces s of a regional HEI, implemented within cross7border cooperation in the Barents Euro Arctic region. The authors analyze the international activities of Murmansk State Humanities University, considered as an area of innovation, promoting HEI’s entrance into the European space of higher education.The article focuses on the international integration and complex projects, in which the university takes part.